Changes in time-continuous joint kinematics in preschool children over the stance phase of gait - Rygelova, Marketa; Uchytil, Jaroslav; Hamill, Joseph; Malus, Jan; Torres, Isaac Estevan; Janura, Miroslav (Gait & posture, 2025)
BACKGROUND: The use of statistical parameter mapping (SPM) to compare gait kinematics of children at different ages seems to be a more appropriate tool to describe the differences than simply describing the maxima and minima on the curves. RESEARCH QUESTION: Does lower limb kinematic waveforms differ during gait in normally developing preschool children? METHODS: In a cross-sectional study, SPM was used to compare kinematic waveforms of typically developing preschool children at ages 2, 3, and 6 years (n = 42). RESULTS: Differences in internal rotation foot angle between 2-year-olds and 3-, 6-year-olds in 22-55 % lower in 2-year-olds but 85-100 % greater in 2-year-olds. Greater internal rotation of the knee in 2-year-olds versus 6-year-olds in 13-25 % of the stance phase. Lower knee abduction in 2-year-olds versus 6-year-olds in the first 13 % of the stance phase. SIGNIFICANCE: Comparison of the waveforms of the angle may provide a clearer understanding of the differences in gait kinematics in children at different ages.
Keywords: Kinematics; Humans; dítě; Child; Female; chůze (způsob); věkové faktory; Range of Motion, Articular; lidé; Children; Gait; předškolní dítě; Statistical parameter mapping; Knee Joint; ženské pohlaví; Male; Develop; Cross-Sectional Studies; Age Factors; biomechanika; rozsah kloubních pohybů; mužské pohlaví; Child, Preschool; Biomechanical Phenomena; průřezové studie; kolenní kloub